Fresh Versus Frozen Stool for Fecal Microbiota Transplantation—Assessment by Multimethod Approach Combining Culturing, Flow Cytometry, and Next-Generation Sequencing - Bilinski, Jaroslaw; Dziurzynski, Mikolaj; Grzesiowski, Pawel; Podsiadly, Edyta; Stelmaszczyk-Emmel, Anna; Dzieciatkowski, Tomasz; Lis, Karol; Tyszka, Martyna; Ozieranski, Krzysztof; Dziewit, Łukasz; Basak, Grzegorz W. (Frontiers in Microbiology, 2022)
The objective of this work was to compare the quality of FMT preparations made from fresh feces with those made from feces frozen in -30oC without any pre-processing or cryopreservation additives. The research hypothesis was that such preservation protocol (frozen whole stool, then thawed and processed) is equipotent to classical fresh FMT preparation. For that, three complementary methods were applied, including: (i) culturing in aerobic and anaerobic conditions, (ii) measuring viability by flow cytometry and (iiii) next-generation sequencing. Flow cytometry with cell staining showed that applied freezing protocol causes significant changes in all of the observed bacterial fractions. Alive cell counts dropped 4 times, from around 70% to 15%, while the other two fractions, dead and unknown cell counts quadrupled and doubled, with unknown fraction becoming the dominant one, with average contribution of 57.47% per sample. It will be very interesting to uncover what this unknown fraction really is (e.g. bacterial spores), as this may change our conclusions (if these are spores the viability could be even higher after freezing). Freezing had a huge impact on the structure of cultivable bacterial communities. The biggest drop after freezing in the number of cultivable species was observed for Actinobacteria and Bacilli. In most cases, selected biodiversity indices were slightly lower for frozen samples. PCoA visualization built using weighted UniFrac index showed no donor-wise clusters, but a clear split between fresh and frozen samples. This split can be in part attributed to the changes in the relative abundance of Bacteroidales and Clostridiales orders. Our results clearly show that whole stool freezing without any cryoprotectants has a great impact on its cultivability and biodiversity of the bacterial community, and possibly also on the viability of bacterial cells.